Arabidopsis VQ MOTIF-CONTAINING PROTEIN29 Represses Seedling Deetiolation by Interacting with PHYTOCHROME-INTERACTING FACTOR1. Issue 4 (25th February 2014) - Li, Yunliang; Jing, Yanjun; Li, Junjiao; Xu, Gang; Lin, Rongcheng
Abstract : A transcriptional regulator interacts with the transcription factor PIF1 to modulate hypocotyl cell growth in response to light . Abstract: Seedling deetiolation, a critical process in early plant development, is regulated by an intricate transcriptional network. Here, we identified VQ MOTIF-CONTAINING PROTEIN29 (VQ29) as a novel regulator of the photomorphogenic response in Arabidopsis ( Arabidopsis thaliana ). We showed that 29 of the 34 VQ proteins present in Arabidopsis exhibit transcriptional activity in plant cells and that mutations in the VQ motif affect the transcriptional activity of VQ29. We then functionally characterized VQ29 and showed that the hypocotyl growth of plants overexpressing VQ29 is hyposensitive to far-red and low-intensity white light, whereas a vq29 loss-of-function mutant exhibits decreased hypocotyl elongation under a low intensity of far-red or white light. Consistent with this, VQ29 expression is repressed by light in a phytochrome-dependent manner. Intriguingly, our yeast ( Saccharomyces cerevisiae ) two-hybrid, bimolecular fluorescence complementation, and coimmunoprecipitation assays showed that VQ29 physically interacts with PHYTOCHROME-INTERACTING FACTOR1 (PIF1). We then showed that VQ29 and PIF1 directly bind to the promoter of a cell elongation-related gene, XYLOGLUCAN ENDOTRANSGLYCOSYLASE7, and coactivate its expression. Furthermore, the vq29 pif1 double mutant has shorter hypocotyls than either of the corresponding single mutants. Therefore, our study reveals that VQ29 is a negative transcriptional regulator of light-mediated inhibition of hypocotyl elongation that likely promotes the transcriptional activity of PIF1 during early seedling development.